Art Learning for Children as a Social Emotional Learning Program - Selvi Rahmadani Pratiwi; Yudi Sukmayadi; Trianti Nugraheni (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Attitude is an aspect that needs attention because it is a polemic problem in children today. This article aims to initiate the concept of art learning as a social emotional learning program. It can be said that art education has a further meaning than just a process of transferring knowledge and skills, but art education can be used as an effort to develop Emotional Intelligence (EQ) and Intellectual (IQ) this is because art education itself is based on mental (moral), analysis, and synthesis, besides that art is seen as having the essential value to touch one's emotional plain. Literature review is the method in this research with data collection techniques from keyword searches: (1) social emotional learning and (2) art learning for children through Google Scholar. The results of the study found that social emotional learning through art education is seen as something interesting and crucial to be studied and further formulated into a formulation, where the concepts of Art Learning and Social Emotional Learning are used as a foothold and then analyzed, and led to the finding that art learning can be used as a social emotional learning program to be able to improve the five domains of children's social emotional competence. This research has implications for children's social emotional development including awareness and appreciation skills as a form of affection that can be applied later in social life.